PENINGKATAN KAPASITAS SDM DALAM MEINGIMPLEMENTASIKAN EKOWISATA BERBASIS KOMUNITAS (COMMUNITY-BASED ECOTOURISM) DI NEGERI SAWAI KECAMATAN SERAM UTARA MALUKU TENGAH - Dian F Nanlohy; Nurlaila Tuanany; Victor D Tutupary; Jean E Ilela (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2020)
The concept of community-based ecotourism emphasizes on efforts to conserve biodiversity by creating close cooperation between local communities and the tourism industry. The fundamental thing in community-based tourism development based on the ecotourism concept is to improve the quality of human resources and skills of local communities around tourist areas. The quality of human resources and community skills are the central issues in this Community Service program. This can be seen in the condition of ecotourism management in Sawai village which is not optimal yet. Activities undertaken include: Establishment of Pokdarwis; Sapta Pesona socialization; Socialization of the development of marine tourism potential; Socialization of ecotourism development on tourist attractions; Study of tourism philosophy and tourism philosophy; Socialization and discussions on the management of statistics on the dynamics and trends of tourism; Socialization of waste management (household waste); Environmental clean activities; and English for Tourism training.